Association between psychological distress and elevated use of electronic devices among U.S. adolescents: Results from the youth risk behavior surveillance 2009-2017. (March 2019) - Wang, Claudia; Li, Kaigang; Kim, Minki; Lee, Shieun; Seo, Dong-Chul
Abstract: Objective: The purpose of this study was to provide updated information about the prevalence and temporal trends of elevated use of electronic devices (EUED) in leisure time (i.e., 3 h or more on an average school day) in nationally representative samples of U.S. adolescents in recent years and to determine whether there is a significant association between EUED and psychological distress. Methods: We used the national Youth Risk Behavior Survey (YRBS) data from 2009, 2011, 2013, 2015, and 2017 ( N = 75, 807). Propensity score matching was used to reduce selection bias due to potential confounding factors with EUED. Ordinal logistic regression analyses were performed for the matched samples to predict the association between EUED and psychological distress. Results: The prevalence of EUED in U.S. youth has substantially increased from 24.9% in 2009 to 43.1% in 2017 ( p < .001). Boys had higher rates of EUED than girls only in 2009 and 2011 but not in 2013, 2015, and 2017. A significant association between EUED and psychological distress was identified throughout all the five survey years. The odds of having a higher level of psychological distress increased approximately 1.5 times among youth with EUED than those without. Conclusions: The prevalence of U.S. youth with psychological distress and EUED has increased simultaneously in the past several years. Future longitudinal studies are warranted to examine causal and/or reciprocal relationship between the two. Highlights: Elevated use of electronic devices (EUED) is increasing in U.S. adolescents. Boys had higher rates of EUED than girls in 2009–2011, not in 2013–2017. There is a significant association between EUED and psychological distress.